Case Report: Multiple Retinal Astrocytic Hamartomas in Congenital Disorder of Glycosylation-Ia - Midena, Giulia; Pilotto, Elisabetta (Frontiers in Medicine, 2022)
Congenital disorder of glycosylation-Ia (CDG-Ia) is a rare autosomal recessive genetic disorder, characterized by systemic and ophthalmological abnormalities. Here, we report multiple retinal astrocytic hamartomas as a new retinal finding in an adolescent affected by congenital disorder of CDG-Ia. A 15-year-old boy affected by CDG-Ia underwent full ophthalmic examination, full field electroretinography (ERG) evaluation and retinal multimodal imaging, including: fundus photography, spectral domain optical coherence tomography (SD-OCT) and blue fundus autofluorescence (FAF). Blue FAF showed multiple papillary and iuxtapapillary bilateral hyper-FAF lesions, corresponding to hyperreflective thickening of the retinal nerve fiber layer, with internal optical empty spaces and posterior dense optical shadowing at SD-OCT. These imaging findings were consistent with retinal astrocytic hamartomas. Scotopic ERG response was significantly reduced in both eyes. Macular edema and absence of the retinal outer segments layer were also detectable. Retinal multi-modal imaging provides additional insights about retinal involvement of patients affected by CDG-Ia. In particular, this case shows the presence of multiple retinal astrocytic hamartomas.